Comparative study of oxytocin bolus and oxytocin infusion during caesarean section - Bannihatti, Teena C.; K. R., Hema; N. M., Pradeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The incidence of postpartum haemorrhage varies from 2-11%. Postpartum haemorrhage complicates approximately 4% of deliveries in most large obstetric services. Postpartum haemorrhage is the third major cause of maternal mortality next to pregnancy induce hypertension (pre-eclampsia) and infection. Prevention, early recognition and prompt appropriate intervention are keys to minimizing its impact. Conventionally loss of more than 500 ml of blood following vaginal delivery and 1000 ml of blood following caesarean section is defined as postpartum haemorrhage. In this study we compared the efficacy of intravenous oxytocin bolus (2 IU) dose followed by infusion (160 mIU/minute) and only i.v. oxytocin infusion following delivery of fetus in elective and emergency LSCS with regard to uterine tone. Methods: This study was a prospective observational study. 200 low risk patients scheduled to undergo elective and emergency caesarean section under spinal anaesthesia in Department of obstetrics and gynecology, SSMC, Tumkur. Group A included i.v. bolus + i.v. injection, group B: i.v. infusion. Results: There was significant drop in haemoglobin and PCV in both group A and group B. But it was comparable among two groups. At 15th minute MBP was 77.2 mm of Hg and 80.04 mm of Hg in Group B. In group A better uterine tone was achieved earlier compared to group B at 2, 5, 10, 20 minutes. Conclusions: It was concluded from this study that oxytocin i.v. bolus with infusion causes earlier attainment of better uterine tone when compared with only infusion.